A quantum dot microspheres-based highly specific and sensitive three-dimensional microarray for multiplexed detection of inflammatory factors. (6th September 2021) - Lv, Yanbing; Xu, Hongke; Wu, Ruili; Xu, Yanxia; Li, Ning; Li, Jinjie; Shen, Huaibin; Ma, Hongwei; Guo, Fang; Li, Lin Song
Abstract: The development trend of in vitro diagnostics is to obtain various biological information from a sample at extremely low concentration and volume, which has promoted its progress in accurate and sensitive multiplexed detection. Here, we developed a single color quantum dot (QD) based three-dimensional (3D) structure matrix microarray and conducted the detection of two inflammatory factors (C-reactive protein (CRP) and serum amyloid A (SAA)) by a self-built fluorescence detection system. This strategy increased detection sensitivity by immobilizing the antibody specifically on the 3D substrate because it captured more than about 7 times of 'effective' antibodies compared to the two-dimensional (2D) plane. Compared to the dual QDs-2D fluorescence-linked immunosorbent assay, the limit of detection (LOD) of 3D microarray based on QDs modified with amphiphilic polymers has been further improved to 0.11 ng ml −1 for SAA assay and to 0.16 ng ml −1 for CRP assay, respectively. By using QD microspheres (SiO2 @QDs@SiO2 -COOH, containing approximately 200–300 hydrophobic QDs on per SiO2 sphere) as fluorescent labels, the LOD for CRP and SAA of 3D microarray reached as high as 15 pg ml −1 and 86 pg ml −1, and the sensitivity was further improved by 28-fold and 425-fold, respectively. Because of its excellent performance, this QD microspheres-based 3D microarray has great application potential for highly sensitive and multiplexed quantitative detection of other biomarkers, small molecules, and antibiotic residues in biomedicine and food safety.